Isoprene Polymerization on Iron Nanoparticles Confined in Carbon Nanotubes. Issue 48 (16th October 2015) - Li, Xiaojian; Zhang, Liping; Tan, Reasmey P.; Fazzini, Pier‐Francesco; Hungria, Teresa; Durand, Jérôme; Lachaize, Sébastien; Sun, Wen‐Hua; Respaud, Marc; Soulantica, Katerina; Serp, Philippe
Abstract: The confinement of air‐protected metallic magnetic nanoparticles in the inner cavity of carbon nanotubes (CNTs) should offer an interesting perspective for biomedical applications or for controlling CNT alignment in composites. Because the direct confinement of polymer‐precoated nanoparticles in CNTs could be restricted by diffusion limitations, we developed a process based on: 1) the confinement of iron nanoparticles surface‐modified with an iron polymerization catalyst in the cavity of CNTs and 2) the polymerization of isoprene on the confined nanoparticles. The resulting material consists in CNT‐confined iron nanoparticles coated with a polyisoprene air barrier. This approach constitutes a proof of concept for the development of smart materials for use in medicine or composites. Abstract : A confined target : Polymerization on magnetic nanoparticles confined in carbon nanotubes (CNTs) has been achieved (see picture). Grafting of an active polymerization catalyst onto the surface of the iron nanoparticles (FeNPs) is the key step in this polymerization, which constitutes a real advance in the development of smart materials for use in medicine or composites.